Comparison of Minimally Invasive Tubular Surgery with Conventional Surgery in the Treatment of Thoracolumbar Metastasis - Cui Y (Dove Medical Press, 2021)
Yunpeng Cui, Xuedong Shi, Chuan Mi, Bing Wang, Yuanxing Pan, Yunfei Lin Department of Orthopaedics, Peking University First Hospital, Beijing, People’s Republic of ChinaCorrespondence: Xuedong ShiDepartment of Orthopedic, Peking University First Hospital, No. 7 Xishiku Street, Xicheng District, Beijing, 100032, People’s Republic of ChinaTel +86 10-83575660Email pku_ortho@163.comBackground: This study aimed to evaluate the perioperative safety and efficacy of minimally invasive tubular surgery for patients with spinal metastasis.Methods: A total of 161 consecutive patients with spinal metastasis between June 2017 and June 2020 were retrospectively reviewed. A total of 36 patients were included in this study, 14 patients underwent minimally invasive tubular surgery (M), and 22 patients underwent conventional surgery (C). T-test and chi-square tests were used to evaluate demographic and perioperative data differences between the two groups.Results: Baseline characteristics did not differ significantly between M and C groups except for the SINS (p=0.002) and preoperative Alb (p=0.026). There was no significant difference in operative time and complications between M and C groups (p< 0.05). The M group had less mean blood loss than the C group (1275 vs 718mL, p=0.045). Blood transfusion was comparable between the two groups (p< 0.05). The mean amount and drainage time were lower than the C group (141 vs 873mL, p< 0.001; 3.1 vs 7.0 days, P< 0.001). The mean postoperative hospitalization of the M group was 8.8 days, which was lower than the C group (11.3 days, p=0.045). Sub-analysis showed that for patients with hyper-vascular tumor, the M group had less mean amount and time of drainage compared with the C group (p< 0.05); for patients with hypo-vascular tumor, the mean blood loss and amount of blood transfusion were also reduced in M group (p< 0.05). The mean blood loss and drainage time of patients with hypo-vascular tumors were less than patients with hyper-vascular tumors in the M group (p< 0.05).Conclusion: In selected cases, minimally invasive tubular surgery is safe and effective for patients with spinal metastasis. Patients with hypo-vascular tumors were more suitable for this technique with less blood loss, fewer blood transfusions, minor drainage, and shorter postoperative hospitalization.Keywords: spinal metastasis, minimally invasive tubular surgery, minimally invasive spine surgery, conventional surgery, tubular retractor, hypo-vascular tumor